2020
DOI: 10.1177/1747954120980712
|View full text |Cite
|
Sign up to set email alerts
|

Maturity timing and performance in a youth national basketball team: Do early-maturing players dominate?

Abstract: The aims of this study were to examine the influence of maturity timing on functional skills and game-related statistics amongst under-16 (U16) national team basketball players, and analyse which of these parameters were related to onward selection to the under-18 (U18) national team. Thirty-six U16 basketball players underwent anthropometric and overhead squat assessments during a national team training camp. Also, maturity offset (MO) was computed alongside game-related statistics during the U16 National Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…The talent identification process has been widely studied in individual and team sports (Johnston et al, 2018;Till and Baker, 2020;Williams et al, 2020). Specifically, basketball studies concluded that motor abilities (Erčulj et al, 2010) and maturational status (te Wierike et al, 2015;Arede et al, 2019bArede et al, , 2020 play an important role in players' selection process and the progress of their careers. The present study revealed that the average number of players who participated in youth championships per generation was around 16 players in the men's category and 12 in the female's category.…”
Section: Discussionmentioning
confidence: 99%
“…The talent identification process has been widely studied in individual and team sports (Johnston et al, 2018;Till and Baker, 2020;Williams et al, 2020). Specifically, basketball studies concluded that motor abilities (Erčulj et al, 2010) and maturational status (te Wierike et al, 2015;Arede et al, 2019bArede et al, , 2020 play an important role in players' selection process and the progress of their careers. The present study revealed that the average number of players who participated in youth championships per generation was around 16 players in the men's category and 12 in the female's category.…”
Section: Discussionmentioning
confidence: 99%
“…Team training camp (height = 180.5 vs. 189.7 cm, body mass = 68.8 vs. 81.1 kg) (Arede et al, 2020). However, it is worth mentioning that U-16 national team players were 3.1 years (early mature) and 2.3 years (average) from PHV (Arede et al, 2020), while our U-16 regional team players were 2.04 years from PHV.…”
Section: Discussionmentioning
confidence: 69%
“…However, when players' heights were compared according to YAPHV, the results presented by local basketball players (height: −0.5 YAPHV = 166.7 cm; 0.2 YAPHV = 167.6 cm) became remarkably similar to those shown in our study (height: “0” YAPHV group = 169.2 cm) (Arede et al, 2021 ). In addition, our U-16 elite regional basketball players seem to be shorter and lighter than the basketball players who were selected to participate in the U-16 Portuguese National Team training camp (height = 180.5 vs. 189.7 cm, body mass = 68.8 vs. 81.1 kg) (Arede et al, 2020 ). However, it is worth mentioning that U-16 national team players were 3.1 years (early mature) and 2.3 years (average) from PHV (Arede et al, 2020 ), while our U-16 regional team players were 2.04 years from PHV.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations